A new method to model dislocation self-climb dominated by core diffusion. (February 2020) - Liu, Fengxian; Cocks, Alan C.F.; Tarleton, Edmund
Highlights: A new methodology is proposed for describing the core diffusion dominated dislocation self-climb process, based on a variational principle for the evolution of microstructures. A dislocation self-climb model is developed by incorporating the finite element core diffusion formulation within the nodal based three-dimensional discrete dislocation dynamics framework, which allows traditional discrete dislocation modelling to be extended to a new class of physical problem. The loop coarsening process during post-irradiation annealing is systematically investigated based on the glide/self-climb model. Graphical abstract: Abstract: The mobility of atoms in dislocation core regions is many orders of magnitude faster than in the surrounding lattice. This rapid atomic transport along dislocation cores plays a significant role in the kinetics of many material processes, including low-temperature creep and post-irradiation annealing. In the present work, a finite element based analysis of the dislocation core diffusion process is presented; based on a variational principle for the evolution of microstructure. A dislocation self-climb model is then developed by incorporating this finite element core diffusion formulation within the nodal based three-dimensional discrete dislocation dynamics framework. The behaviour of an isolated loop in bcc iron is briefly reviewed, and simulations are extended to include the loop coarsening processes of both parallel and non-parallel loops by self-climb plus glide mechanisms, in which the huge time scale separation between climb and glide is bridged by an adaptive time stepping scheme. Excellent agreement is obtained between the numerical simulation, the theoretical solution of rigid prismatic loops and published experimental results. The coarsening process of a population of loops is simulated to investigate the mechanisms of the accumulative interactions and large-scale-patterning in bcc materials.